079 Genetic testing in epilepsy: a new imperative for precision. Issue 12 (14th November 2019) - Scott, Nicholas; Hamilton, Leigh; Symonds, Joe; Heath, Craig; Abbasi, Hina; Goldberg, Danielle; Hewitt, Russell; Marshall, Victoria; Zuberi, Sameer; Leach, John Paul
Abstract : We reviewed the results of testing in patients from the West of Scotland attending adult epilepsy clinics with MRI-negative drug-resistant epilepsies or epilepsies with co-morbid intellectual disability, Methods: 45 eligible (>18y) cases were referred for testing. Clinicians completed a structured electronic clinical referral proforma to aid variant interpretation. Cases were tested on a custom-designed 104-gene panel focusing on disorders for which MRI would not provide a diagnosis. Variants were classified using UK Association of Clinical Genetic Science Guidelines. Variants of uncertain significance (VUS), likely pathogenic, and definitely pathogenic variants were discussed by a multidisciplinary team. Diagnostic variants were confirmed by Sanger sequencing. Results: Among 45 cases, likely pathogenic and pathogenic (diagnostic) variants were identified in 8 (18%), with VUS in 10 (22%). Pathogenic variants were identified in the following genes; GAMT, CHRNB2, SCN2A, PCDH19, PRRT2, SLC2A1, SCARB2, and SBTX1B. All cases with abnormal results or VUS were offered referral to a Genetic Epilepsy Clinic for counselling. Genetic findings altered therapy in several cases: some with VUS became seizure-free with targeted changes in treatment. Determination of clinical significance was sometimes helped by further familial testing. Conclusion: Genetic testing is an essential tool in the management of adult patients with drug-resistant epilepsy, particularly those with childhood onset and/or accompanying learning difficulties. Abnormalities can be expected in approximately 40% using these criteria, which can aid both management and family counselling.